Osteosarcoma of the larynx - Sawicki, Piotr; Każmierczak, Wojciech; Szylberg, Łukasz; Marszałek, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2015)
Malignant neoplasms of the larynx are divided into epithelial and non-epithelial. Non-epithelial neoplasms include, among others, mesenchymal chondrosarcomas and osteosarcomas. Few cases of laryngeal osteosarcomas described in the literature were usually treated by surgery without the need to use adjuvant radio- or chemotherapy. Few authors propose the initial application of radiotherapy or high-dose chemotherapy. Our study presents a very rare case of a woman treated due to laryngeal osteosarcoma. We have also presented diagnostic difficulties preceding a decision to perform radical surgery. The patient had been eligible for radical surgical treatment, even though there were no features of malignancy in a histopathological examination of the biopsy material. Complete laryngectomy was carried out without the surgery of the cervical lymphatic system. Laryngeal osteosarcoma was diagnosed based on the postoperative histopathological examination using vimentin and Ki67. The patient remains under the care of the Otolaryngology and Laryngological Oncology Department and Oncology Centre in Bydgoszcz. There were no reports on local recurrence or distant metastases during regular check-ups